Antibacterial activity of Parkia speciosa Hassk pod crude extract against Pseudomonas fuscovaginae - Kah, Oi Yuan (2016)
Rice is one of the most important food crops that feed almost over 3 billion of people worldwide. However, the outbreak of pest and diseases affected the world rice production. One of the serious infection on paddy plant is Bacterial Sheath Brown Rot caused by Pseudomonas fuscovaginae. Pseudomonas fuscovaginae is a florescent gram negative pathogenic bacterium. Several control methods had been carried out and found to be effective toward Pseudomonas fuscovaginae yet does not completely eliminate the pathogen from the plant. Parkia speciosa Hassk has been used as folk medicine to treat various human diseases and sickness. Alkaloid, Saponin, Terpenoids, Phenolic, Flavonoid, and Tannin were the phytochemical substances that can be found in all parts of Parkia speciosa plant. Several research had found that methanolic extract of Parkia speciosa pod can inhibit the growth of bacteria Staphylococcus aureus and Escherichia coli. However, there is no research on antibacterial activities of this plant extract toward plant pathogenic bacteria. This study is to identify the antibacterial activities of Parkia speciosa pod extract toward Pseudomonas fuscovaginae and to determine the active chemical compounds in the Parkia speciosa pod. Methanolic pod extract of Parkia speciosa with concentration of 25, 50, 100, 150, 200,250, 300, 350, and 400mg/mL were tested on the pathogenic bacteria for antibacterial activities using agar well diffusion assay. Streptomycin sulfate was used as positive control while methanol used as negative control. Phytochemical analysis was done by using standard method. The inhibition zone of the extract show positive results such as 1.90cm, 2.00cm, 2.00cm, 2.00cm, 2.00cm, and 1.92cm on concentration 100, 150, 200, 250, 300 and 350mg/ml respectively. Flavonoid, saponin, terpenoid, and tannin were present in Parkia speciosa pod extract. Pyrogallol which is known as antimicrobial chemical compound was identified in Parkia speciosa crude extract using Gas chromatography–Mass spectrum analysis.